Menelaah Penerapan Hukum Taurat secara Progresif Dalam Matius 5:17-20 - Boko, Irenius Pita Raja; Senda, Siprianus S.; Boy, Mikhael Valens (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
Torah are the norms or rules of life of every aspect in the society of Israelites. It is associated also with the covenant which made between God and His chosen nation, the Israelite. In the journey of history, this Torah was contextualized with the Jewish people. The Jews interpret the Torah as a visible instrument for them to lead them to obtain eternal life in the future. However, the Pharisees and scribes understood the Torah in a positivistic way. Therefore, based on the text of Matthew 5:17-20, and by using qualitative methods with a literature approach, the article will review and discuss Jesus as a figure who progressively realized the Torah. The basic for the progressive realization of Torah is love. Furthermore, the progressive realization of Torah makes law in the sense of humanizing the human beings.